(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crime is a social phenomenon, which means that crime cannot be abolished; it can be regulated by crime prevention initiatives implemented by authorities. Crime is a major problem that affects everyone in society. It is a problem for today’s society that can have long-term consequences for victims, their families, and communities. The purpose of the study is to determine the level of crime prevention programs in Barangay 176 Bagong Silang, Caloocan City, as well as to understand their effect on society in general. It also aims to find out what prevention is the most effective. Community crime prevention programs or strategies target changes in the community, culture, or the physical environment in order to reduce crime in the future. This study will also be an eye-opener for barangay officials of barangay 176 Bagong Silang Caloocan City, showing that prevention programs are very valuable in preventing crimes in the future. This study also aims to enhance their ways of how maintaining the peace and order of their barangay. This would help and add up further details and information that are useful for our research since this research already has the information they seek, therefore making our research easy. Measures - Rank one, “reducing opportunities for crimes to be committed,” with a total mean score of 3.68, interpreted as Strongly Agree. Rank two. “Improving the ability of barangay personnel,” with a mean score of 3.63, was interpreted as strongly Agreeable. Rank three, “Strategy of barangay for crime prevention,” with a total mean score of 3.55, interpreted as Strongly Agree. Rank four, “Implementing of peace and order in barangay,” with a total mean score of 3.40, interpreted as Strongly Agree. Rank five, “Increasing surveillance installing locks and alarms,” with a total mean score of 3.38, interpreted as Strongly Agree. In terms of indicators above in Barangay Officials, the indicators showed that the “Increasing surveillance installing locks and alarms” with a weighted mean of 3.65 interpreted as Strongly Agree, next is “Improving the ability of barangay personnel with weighted mean of 3.5 interpreted as Strongly Agree and “Strategy of barangay for crime prevention” with the weighted mean of 3.45 interpreted as Strongly Agree and “Reducing opportunities for crimes to be committed” the with weighted mean of 3.40 interpreted as Strongly Agree, lastly, “Implementation of peace and order in barangay” with weighted mean of 3.25 interpreted as Agree. In terms of indicators above in Police Officers, the indicators showed “Reducing opportunities for crimes to be committed” with a weighted mean of 3.95, interpreted as Strongly Agree; next is “Improving the ability of barangay personnel” with a weighted mean of 3.75 interpreted as Strongly Agree and “Implementation of peace and order in barangay” with the weighted mean of 3.70 interpreted as Strongly Agree and “Strategy of barangay for crime prevention” with weighted mean of 3.65 interpreted as Strongly Agree”, lastly, “Increasing surveillance installing locks and alarms” with weighted mean of 3.10 interpreted as Agree. This research would be a great help and give ideas to the government to increase their crime prevention programs to where they are lacking and give them more ideas. This research would help the students be aware of the situation in their communities, especially those in the municipality of Caloocan City. This would help the police department to understand or further the information that could be found in this research. This aimed primarily to determine the effectiveness of crime prevention strategies implemented by the Philippines National Police (PNP) in terms of police integrated patrol system, barangay peacekeeping operation, anti- criminality operation, and integrated area community public services. Crime prevention strategies and measures aim to reduce the likelihood of crimes occurring as well as their potentially harmful effects on individuals and society, including fear of crimes, by intervening to influence their multiple causes. Barangay response is fundamentally about and for communities. As a result, we must always consider the public option when establishing crime prevention priorities and devising appropriate responses; the promotion of community safety processes in terms of reassurance and barangay response were frequently mentioned as important factors with the right response at the right time, the public expected greater barangay engagement, which would impact crime and fear of crime. The police are primarily responsible for the maintenance of public order. The industry of crime prevention and detection.